Automatic Lamps A Light Over the Ancient Iranian Knowledge - Yousef Yassi; Safar Hashemlo; Mohmmad Bayrami; Fatemeh Tabatabaei; Azadeh Karimi (آموزش مهندسی ایران, 2010)
From the one hundred inventions and innovations presented in the book “Al-Hiyal", lamps have unique and No comparable designs in their mechanisms in comparison with other samples. “Al-Hiyal" is the title of a book which has been written in the 10th century A.C. by Ahmad Ibn Musa. He was one of the three sons of Musa ibn Shaakir Khorassani who are known as "¬Banu Musa" by the historians and scientists. They are the most famous and out standing Iranian scientists of the Islamic era. All of his innovations and inventions have been presented in the hand written versions of the book "Al-Hyial". Redesign, remanufacture and testing the applied mechanisms of these lamps are parts of a research project undertaken by the Mechanical Engineering Research Center of the Iranian Research Organization for Science and Technology. In this article all the mechanisms applied in these lamps from design view point have been appraised and discussed. However during the course of this project “a progressing design process” in innovative thinking of Ahmad ibn Musa has been observed. This achievement is the most important outcome of this project which ought to be taught in engineering courses. However, all the lamps were redesigned and manufactured according to the details presented in the book. Tests results of the manufactured samples showed perfect agreement between the outcomes of the tests and the performance mentioned in the book.